Analysis of the Employment Law Policy for Foreigners in Indonesia in the Job Creation Law Viewed from an Islamic Law Perspective, Fathu Dzariah Wa Saddu Dzariah Rules - Benanda Bunga Natasha; M. Junaidi (Universitas Muhammadiyah Surakarta, 2023)
On January 22 2020 the DPR RI inaugurated the Draft Law (RUU) which included the Job Creation Bill. The inauguration of the Job Creation Bill under the leadership of President Joko Widodo aims to provide investment breakthroughs in the economic sector in Indonesia, so that it can compete with other countries. But it is very unfortunate that the steps and goals that were expected to bring progress and goodness to the Indonesian state have instead become a frightening specter among Indonesian society. The specter in question is the contents of the Omnibus Law in the Job Creation Law which provides freedom and ease for foreign workers to enter Indonesia. Meanwhile, on the other hand, there are laws which are felt to have overlapping roles, namely between Presidential Decree Number 20 of 2018 and Law Number 13 of 2003 relating to the obligation for foreign workers entering Indonesia to have written permission from the Minister or appointed official who ratifies it. According to the background of the problem above, there is a fundamental problem that will be discussed, namely how is the analysis of the Job Creation Law regarding foreign employment in Indonesia viewed from the perspective of Islamic law using the rules of Fathu Dzariah wa Saddu Dzariah? With a phenomenon like the one above, Islamic Law provides confirmation that the policy implemented by the government regarding the new regulations governing foreign workers to enter Indonesia more easily is something that causes harm even though it has a good aim for the Indonesian economy, but The bad impacts it causes are more than the good impacts on society.